Electricity outages in Ghana: Are contingent valuation estimates valid?. (December 2019) - Amoah, Anthony; Ferrini, Silvia; Schaafsma, Marije
Abstract: African countries experience persistent and serious energy outages, but while multiple valuation studies provide estimates of the costs of electricity outages in high-income countries, evidence is scarce for lower- and middle-income countries. The few studies that assess the value of reliable energy supply rely on the contingent valuation method that is under wide scrutiny. This paper aims to provide new estimates of households' willingness to pay to reduce electricity outages for Ghana and contributes to the debate on the validity of contingent valuation results for energy reliability. Our results suggest that households are willing to pay GHS 67 ($17) per month for reliable electricity supply, equivalent to 7% of respondents' income. The results of tests for hypothetical bias, WTP-WTA disparity and income effects suggest that the contingent valuation estimates from this study are robust and can support decision makers in prioritizing energy policies and investments. Highlights: Estimates for electricity outages in Lower and Middle Income countries (LMIC). Households' losses to due electricity outages in Ghana. The validity of contingent valuation estimates for electricity outages. Households are willing to pay $0.09/KWh to secure reliable electricity access. Robust estimates of electricity outages for energy policy decision making.